Immunohistochemical detection of lymph node‐DTCs in patients with node‐negative HNSCC. Issue 9 (8th February 2017) - Sproll, Christoph; Freund, Anna Karen; Hassel, Andrea; Hölbling, Marianne; Aust, Verena; Storb, Sebastian H.; Handschel, Jörg; Teichmann, Carina; Depprich, Rita; Behrens, Bianca; Neves, Rui Pedro Lousa; Kübler, Norbert R.; et al.
Abstract : This study was performed to systematically assess the prevalence, topography and prognostic impact of disseminated tumor cells (DTCs) in lymph nodes (LN) of patients with primary, regional and distant metastasis‐free head and neck squamous cell carcinoma (HNSCC) who underwent resection with elective neck dissection. From the routinely processed resection specimen, we could prospectively analyze a total of 1.137 exactly mapped LNs of 50 pN0‐HNSCC patients, classified as tumor free by routine histopathology. Three immunohistochemistry (IHC) assays using antibodies directed against CK5/14, a broad spectrum of CKs (1–8, 10, 14–16 and 19), and CD44v6, respectively, were applied on 4.190 LN sections to detect DTCs. The IHC results were correlated with clinicopathologic parameters and clinical follow‐up data. We detected seven micrometastases (MM) in five patients and 31 DTCs in 12 patients. Overall, 15 (30%) patients were positive for DTCs or MMs. Strikingly, the anatomical distribution of LN affected with DTCs was not random, but was dependent on the lateralization of the primary tumor and clustered significantly most proximal to the primary tumor. None of the investigated patients developed loco‐regional lymphatic or distant metastasis during the mean follow‐up period of 71 months. Our results reveal clinically occult tumor cell dissemination as an early and frequent event in HNSCC. Considering that higher rates of recurrences in therapeutic LN dissection concepts have been reported than in elective neck dissection strategies, our DTC‐data support to perform elective neck dissections, since they appear to be effective in preventing loco‐regional lymphatic recurrence from LN DTCs or MMs. Abstract : What's new? Localized early‐stage head and neck squamous cell carcinoma (HNSCC) is curable through surgical resection. Not infrequently, however, HNSCC returns in the form of locoregional relapse or distant metastases. Here, analyses of patient resection specimens show that clinically occult lymphatic tumor cell dissemination can occur earlier than previously assumed, with disseminated tumor cells (DTCs) already present in UICC stage I and II tumors. Topographical analysis of lymph nodes (LN) harboring DTCs revealed nonrandom distribution following the typical dissemination pattern of HNSCC metastases. The findings warrant investigation of sentinel LN testing and elective neck dissection to prevent HNSCC recurrence.